SILICATE-SALT (SULFATE) LIQUID IMMISCIBILITY: A STUDY OF MELT INCLUSIONS IN MINERALS OF THE MUSHUGAI-KHUDUK CARBONATITE-BEARING COMPLEX (SOUTHERN MONGOLIA) - Andreeva I.A.; Kovalenko V.I.; Naumov V.B. (My University, 2007)
Crystalline and melt inclusions were studied in garnet, diopside, potassium feldspar, and sphene from the garnet syenite porphyry of the carbonatite-bearing complex Mushugai-Khuduk, southern Mongolia. Phlogopite, clinopyroxene, albite, potassium feldspar, sphene, wollastonite, magnetite, Ca and Sr sulfates, fluorite, and apatite were identified among the crystalline inclusions. The melt inclusions were homogenized at 1010 - 10809°C and analyzed on an electron microprobe. Silicate, salt, and combined silicate-salt melt inclusions were found. Silicate melts show considerable variations in SiO2 concentration (56 to 66wt%), high Na2O + K2O (up to 17wt%), and elevated Zr, F, and CI contents. In terms of bulk rock chemistry, the silicate melts are alkali syenites. During thermometric experiments, salt melt inclusions quenched into homogeneous glasses of predominantly sulfate compositions containing no more than 1.3wt% SiO2. These melts are enriched in alkalis, Ba, Sr, P, F, and Cl. The investigation of the silicate and salt melt inclusions in minerals of the garnet syenite porphyries indicate that these rocks were formed under influence of the processes of crystallization differentiation and magma separation into immiscible silicate and salt (sulfate) liquids.
Keywords: ALKALINE ROCKS; CARBONATITES; CRYSTAL FRACTIONATION; LIQUID IMMISCIBILITY; SILICATE AND SALT MELT INCLUSIONS